This preview shows page 1. Sign up to view the full content.
Unformatted text preview: Yc=f(x) c > 1 vertical compression Yc=f(x) c < 1 vertical stretch Composition: Y=f(x): FoG(x) = f[g(x)] usually these two are not the same, Y=g(x): GoF(x) = g[f(x)] unless they are inverses ex: f(x) = cos x g(x) = 3x^2+2 FoG(x)= cos[g(x)] = cos (3x^2+2) GoF(x) = 3[f(x)]^2+2 = 3cos^2x+2...
View
Full
Document
This note was uploaded on 04/07/2008 for the course MATH 161 taught by Professor Algier during the Spring '08 term at Grove City.
 Spring '08
 Algier

Click to edit the document details